MCNP modelling of a neutron generator and its shielding for PGNAA in mineral exploration. Issue 1 (1st December 2019) - Petrovic, Snezana; Carson, Michael
Summary: This paper present results of Monte Carlo simulations of shielding design against neutron and gamma-rays from a D-D 2.5MeV neutron generator. The generator will be located in a restricted access laboratory at the Department Of Exploration Geophysics at Curtin University. To protect staff and students from radiation we need to calculate shielding characteristics needed to reduce the effective dose, from the generator, to safe limits. Since operation facility is of limited dimensions, shielding needs to be optimised in terms of it thickness and the cost as well. Shielding calculations were made using the MCNP6.1 Monte Carlo code. We were required by Radiological Council of Western Australia to put sufficient shielding to achieve a conservative dose constraint for non-radiation workers of 0.5 mSv per year or 9.6 μSv in a week. The shielding was modelled as a hollow sphere of varying shielding thickness of borated polyethylene (BPE), concrete and lead (Pb). Our goal was to determine thickness of concrete needed to decrease the effective dose below prescribed limits. We already purchased 15cm thick BPE and 2.2mm Pb slabs. As a result, we concluded that 15cm thick concrete shielding will be enough to safely operate neutron generator. Our neutron generator will be one of the main components of our proposed prompt gamma neutron activation (PGNA) logging-while-drilling (LWD) tool. This tool should be able to reliably identify the major elements of rock units, including the presence of metallic ores. The availability of such real-time information should improve almost every stage of mining and mineral processing.